Identification of two rate-limiting steps in the degradation of partially folded immunoglobulin light chains - Mann, Melissa J.; Flory, Ashley R.; Oikonomou, Christina; Hayes, Candace A.; Melendez-Suchi, Chris; Hendershot, Linda M. (Frontiers in Cell and Developmental Biology, 2022)
Antibody monomers are produced from two immunoglobulin heavy chains and two light chains that are folded and assembled in the endoplasmic reticulum (ER). This process is assisted and monitored by components of the endoplasmic reticulum quality control (ERQC) machinery; an outcome made more fraught by the unusual genetic machinations employed to produce a seemingly unlimited antibody repertoire. Proper functioning of the adaptive immune system is as dependent on the success of this operation, as it is on the ability to identify and degrade those molecules that fail to reach their native state. In this study, two rate-limiting steps were identified in the degradation of a non-secreted κ light chain. Both focus on the constant domain (CL), which has evolved to fold rapidly and very stably to serve as a catalyst for the folding of the heavy chain CH1 domain. The first hurdle is the reduction of the disulfide bond in the CL domain, which is required for retrotranslocation to the cytosol. In spite of being reduced, the CL domain retains structure, giving rise to the second rate-limiting step, the unfolding of this domain at the proteasome, which results in a stalled degradation intermediate.